2019
DOI: 10.1016/j.ijchp.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties and measurement invariance of the Weight Self-Stigma Questionnaire and Weight Bias Internalization Scale in children and adolescents

Abstract: Background/Objective Given the negative consequences of weight bias, including internalized weight stigma, on health outcomes, two instruments—the Weight Self-Stigma Questionnaire (WSSQ) and Weight Bias Internalization Scale (WBIS)—have been developed. However, their psychometric properties are yet to be tested for Asian pediatric populations. Method:Participants aged 8 to 12 years ( N = 287; 153 boys) completed the WSSQ and the WBIS, and they were classified into either a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 46 publications
6
69
1
Order By: Relevance
“…When the measurement invariance is supported, data from different groups (e.g., males and females) are organized according to the same factor structure and make the group comparison meaningful [38][39][40][41]. The measurement invariance is supported by ∆CFI > − 0.01, ∆SRMR < 0.01, and ∆RMSEA < 0.015 in the nested models of configural model, model with loadings constrained, and model with loadings and intercepts constrained [42]. For the internal consistency, the KR20 > 0.7 is recommended; and for test-retest reliability, the ICC > 0.4 is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…When the measurement invariance is supported, data from different groups (e.g., males and females) are organized according to the same factor structure and make the group comparison meaningful [38][39][40][41]. The measurement invariance is supported by ∆CFI > − 0.01, ∆SRMR < 0.01, and ∆RMSEA < 0.015 in the nested models of configural model, model with loadings constrained, and model with loadings and intercepts constrained [42]. For the internal consistency, the KR20 > 0.7 is recommended; and for test-retest reliability, the ICC > 0.4 is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the SBS structure is not influenced by the different subcultures between Iran and Afghanistan. Therefore, the SBS total scores can be used to compare the difference between Iranian and Afghanistani samples (Lin et al 2012;Pakpour et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, prospective studies for children and adolescents are lacking. In cross-sectional studies, more pronounced body dissatisfaction is reported to be associated with higher WBI scores [16,19], and several studies have found a negative correlation between self-esteem and WBI [11,18,20,21]. Just one study that included only children with overweight reported no significant association between self-esteem and WBI [22].…”
Section: Introductionmentioning
confidence: 99%